2003
DOI: 10.1159/000076821
|View full text |Cite
|
Sign up to set email alerts
|

Does <i>Rbmy</i> have a role in sperm development in mice?

Abstract: The Yd1 deletion in mice removes most of the multi-copy Rbmy gene cluster that is located adjacent to the centromere on the Y short arm (Yp). XYd1 mice develop as females because Sry is inactivated, probably because it is now juxtaposed to centromeric heterochromatin. We have previously produced XYd1Sry transgenic males and found that they have a substantially increased frequency of abnormal sperm. Staining of testis sections with a polyclonal anti-RBMY antibody appeared to sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…A recent study carried out with 52 different tissues and more than 10,000 genes showed that testis has the highest rate of divergence in alternative splicing events between human and mouse (Kan et al , 2005). Our findings might explain why the mRBMY seems to have a function different from that of the hRBMY (Szot et al , 2003), as both proteins might have different RNA targets. However, we cannot rule out that the natural hRBMY target sequences differ significantly from the stem–loop motifs we identified by SELEX.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study carried out with 52 different tissues and more than 10,000 genes showed that testis has the highest rate of divergence in alternative splicing events between human and mouse (Kan et al , 2005). Our findings might explain why the mRBMY seems to have a function different from that of the hRBMY (Szot et al , 2003), as both proteins might have different RNA targets. However, we cannot rule out that the natural hRBMY target sequences differ significantly from the stem–loop motifs we identified by SELEX.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, Sly underlies the ChrY deletion mutation phenotypes in mice that exhibit a range of deficiencies in spermatogenesis depending on the extent of the deletion (Reynard et al 2009). Rbmy is also important during spermatogenesis and encodes an RNA-binding protein that regulates mRNA splicing, and loss of RBMY expression may contribute to sperm abnormalities in mice and humans (Elliott et al 2000;Szot et al 2003;Skrisovska et al 2007;Zeng et al 2008;NavarroCosta et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To manipulate the expression of Y genes, it is possible to decrease expression by using a mouse strain that is deficient in the region of the Y chromosome containing that gene (although such mice usually lack several Y genes) and then add back an individual Y transgene inserted onto an autosome (Szot et al, 2003).…”
Section: Mice Transgenic For X or Y Genesmentioning
confidence: 99%